2001
DOI: 10.1111/1475-5661.00036
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the New Deal: local disparities in the performance of Welfare‐to‐Work

Abstract: In recent years, following the lead of the US, several OECD countries have introduced 'workfare' policies that link receipt of unemployment and related social benefits to compulsory participation on state-administered work and training schemes. The UK's New Deal (Welfare-to-Work) for Young People is one of the largest and most developed of these workfare programmes. Official evaluations of the UK's New Deal for Young People claim that it has been a national success, but overlook local variations in its results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 4 publications
1
32
0
Order By: Relevance
“…Those successful in finding work through employment service providers have been observed to be distinguished by their good health, stable housing, experience or qualifications and location in an area where suitable jobs were available (Murphy et al 2011: 114). Some research has also suggested that those with precarious attachment to the labour market may misunderstand employer expectations or have skills that do not match industry needs (Hershey & Pavetti 1997;Sunley et al 2001;OECD 2006 Discrimination against disadvantaged people may be overt, and even where it is not, employers may be uneasy about employing disadvantaged people (Fowkes 2011).…”
Section: Explaining Poor Job Retentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those successful in finding work through employment service providers have been observed to be distinguished by their good health, stable housing, experience or qualifications and location in an area where suitable jobs were available (Murphy et al 2011: 114). Some research has also suggested that those with precarious attachment to the labour market may misunderstand employer expectations or have skills that do not match industry needs (Hershey & Pavetti 1997;Sunley et al 2001;OECD 2006 Discrimination against disadvantaged people may be overt, and even where it is not, employers may be uneasy about employing disadvantaged people (Fowkes 2011).…”
Section: Explaining Poor Job Retentionmentioning
confidence: 99%
“…Some have argued that 'work first' approaches to activation have overemphasised the personal deficits of unemployed people and focused on disciplining non-compliance, rather than integrating job search and basic preparation with more supportive measures aimed at skill development and mobility into better quality jobs (Peck & Theodore 2000;Sunley et al 2001;OECD 2006;Watson 2008;Perkins 2010). Some have argued that 'work first' approaches to activation have overemphasised the personal deficits of unemployed people and focused on disciplining non-compliance, rather than integrating job search and basic preparation with more supportive measures aimed at skill development and mobility into better quality jobs (Peck & Theodore 2000;Sunley et al 2001;OECD 2006;Watson 2008;Perkins 2010).…”
Section: Strategies To Support Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the futility of increasing levels of training (and compulsion) in the absence of local job opportunities has been illustrated by SUNLEY ET AL. (2001).…”
Section: Introductionmentioning
confidence: 99%
“…This work highlighted the intersection of employment and gender relations, the ways in which ethnicity and nationality impact upon work, and the importance of age/generation differences in labour market experience (Hanson and Pratt 1998; McDowell 1997, 2003, 2005, 2006; Raghuram and Kofman 2004). Moreover, important studies also illuminate the ways in which labour markets are regulated and new narratives of class are deployed (Haylett 2003; Peck 1996, 2001; Sunley, Martin and Nativel 2001).…”
mentioning
confidence: 99%